Managing Director's Action Plan to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2012)
As described in the latest Consolidated Multilateral Surveillance Report, policy actions in Europe and improving U.S. indicators have helped attenuate financial strains. But recent developments point to the fragility of the world economy and the need to come to grips with a formidable policy agenda. Among the challenges ahead are the immediate risks from a return of stresses in Europe and higher oil prices. Beyond that lie the risks from protracted low growth, too rapid fiscal consolidation in certain cases, deleveraging and uncertain medium-term policy frameworks in some key advanced countries. Many emerging markets may have to deal with inflation risks, elevated oil prices, the resurgence and volatility in capital inflows, and the consequences of extended credit booms. Delays in implementing global regulatory reforms also pose risks.